Changes in optic nerve head microvasculature following disc hemorrhage absorption in glaucomatous eyes - Jooyoung Yoon; Kyung Rim Sung; Ko Eun Kim; Hyo Ji Han; Joon Mo Kim (Scientific Reports)
Abstract This study investigated the changes in optic nerve head (ONH) microvasculature, circumpapillary retinal nerve fiber layer (cpRNFL) thickness, and visual field (VF) sensitivity following the absorption of optic disc hemorrhage (DH). Intradisc vessel density (dVD) was calculated using a 3 × 3 mm optic disc scan in 60 eyes of 60 patients with primary open angle glaucoma and DH who had undergone two or more swept-source optical coherence tomography angiography exams. Clinical parameters at the time of DH occurrence and after absorption, as well as those between the subgroups based on DH recurrence and location, were compared. Linear regression analysis was performed to identify factors associated with changes in cpRNFL thickness in the DH-affected quadrant. Mean dVD, cpRNFL thickness, and VF sensitivity significantly decreased after DH absorption (all P < 0.05). The reduction in dVD was more pronounced in eyes with recurrent DH compared to those with a single episode (P = 0.032). Eyes with DH occurring within or at the margin of the disc cup showed a greater dVD reduction than those with DH occurring outside the disc cup (P = 0.049). The reduction in cpRNFL thickness in the DH-affected quadrant correlated with dVD reduction in the same quadrant (β = 0.370, P = 0.013) and DH recurrence (β = -2.617, P = 0.033). This finding suggests that DH pathogenesis may be associated with changes in optic disc vasculature, contributing to glaucomatous progression.